2003
DOI: 10.1007/s007740300014
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for osteoporosis in men

Abstract: We evaluated the risk factors for osteoporosis in men. The subjects of this study consisted of 686 healthy middle-aged (40-59 years) men who had undergone bone mineral density (BMD) measurement and medical examination, including physical strength. BMD of L2-4 was measured at the anterior-posterior position, using dual X-ray absorptiometry. Physical investigations, such as height, weight, and physical strength, were carried out on the examination day. Details of tobacco and alcohol consumption, exercise, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 23 publications
1
24
1
2
Order By: Relevance
“…Muscular strength relates to bone mineral in men in some [19][20][21][30][31][32][33][34], but not all [34,35], studies. The findings of this study show that knee extensor strength consistently positively related to bone mineral in middle-age men, but not older men; however, the association between bone mineral and muscular strength is confounded by BFLM.…”
Section: Discussionmentioning
confidence: 98%
“…Muscular strength relates to bone mineral in men in some [19][20][21][30][31][32][33][34], but not all [34,35], studies. The findings of this study show that knee extensor strength consistently positively related to bone mineral in middle-age men, but not older men; however, the association between bone mineral and muscular strength is confounded by BFLM.…”
Section: Discussionmentioning
confidence: 98%
“…Subjects exposed to tobacco, both actively and passively, have been found to be at increased risk for many health problems, including decreased bone mass and increased risk of osteoporotic fractures (Blum et al, 2002;Izumotani et al, 2003;OrtegoCenteno et al, 1997). Osteoporosis is a systemic skeletal disorder characterized by low bone mineral density (BMD) and fragility of the bones, with an attendant increase in the risk of fracture.…”
Section: Introductionmentioning
confidence: 95%
“…Although tobacco exposure has been implicated as a risk factor for osteoporosis in some populations (Blum et al, 2002;Izumotani et al, 2003;OrtegoCenteno et al, 1997), it has not been included consistently in multivariate regression models. The availability of BMC, as determined by DXA in a large U.S. probability sample in conjunction with serum cotinine, a well-accepted marker for tobacco exposure, and other factors believed to be associated with low BMC provides an opportunity to obtain a fuller picture of the tobacco-BMC relationship.…”
Section: Introductionmentioning
confidence: 97%
“…We also showed that TRAP-5b was negatively correlated with Ca in women (β = −0.059, P = 0.039). Because it is well known that ALP is a classical marker for osteoid formation and calcification, and that Ca is important to maintain bone density and is lost with aging especially in women (Hannan et al 2000;Izumotani et al 2003;Meier et al 2005;Lanham-New 2008;Hien et al 2008), our present results suggest that TRAP-5b is a sensitive marker for screening for BMD in the general population of elderly individuals, especially women.…”
Section: Discussionmentioning
confidence: 60%